Skill gaps in young workers in Ecuador - Hermida , Priscila (2023)
This study analyzes the skills deficit in formal sector companies using information on 799 firms obtained from the Structural Business Survey (ENESEM 2018). The skills studied through a Probit model are Reading and Writing, Arithmetic and Problem Solving. The results indicate a correlation between the incidence of gaps and the asymmetry of information on the worker’s skill endowment, and the company’s ability to appropriate the return of on-the-job training, as well as the presence of sectoral heterogeneity in skill deficits. The mismatch between supply and demand for skills is greater in the Manufacturing sector. The findings suggest that improving the quality of information on workers’ skills, and mechanisms that allow companies and individuals to share the costs and returns of on-the-job training, would improve the productivity of the economy.